Will the COVID-19 outbreak be a turning point for China's wildlife protection: New developments and challenges of wildlife conservation in China. (February 2021) - Huang, Qiongyu; Wang, Fang; Yang, Hongbo; Valitutto, Marc; Songer, Melissa
Abstract: On 24 February 2020, at the brink of the global coronavirus disease 2019 (COVID-19) pandemic, the Chinese legislature adopted a decision to ban all terrestrial wildlife for food consumption. This decision set the tone for the revision of the Wildlife Protection Law (WPL), planned for release in late 2020. Both the terrestrial wildlife ban and revised WPL have the potential to greatly reduce consumption of wildlife and aid in prevention of future zoonotic disease outbreaks. The government still faces severe challenges in reducing wildlife use in traditional medicine, strengthening habitat and ecosystem conservation, committing to long-term WPL enforcement, and promoting community education and institutional reforms. However, recent progress in establishing a stricter ban on wildlife consumption, consolidating fragmented protected areas, and increased openness to public oversight are promising developments. While it is clear that global pandemics like COVID-19 can cause massive human suffering and disruption of economies; governments can no longer allow business as usual for the wildlife industry, regardless of the monetary or cultural values it brings. Here we discuss the latest development and limitations of the current wildlife legislation in China and the recommendations for improving Chinese wildlife conservation to better protect biodiversity and reduce risks of spreading zoonotic diseases to humans.